Guest Editorial: Special Issue on "Current Trends and the Future of Internet of Things (IoT) in Industry and Enterprise" - García Díaz, Vicente; Chun-Wei Lin, Jerry; Morente-Molinera, Juan Antonio (Journal of internet technology, 2022)
The Internet of Things (IoT) has become an inevitable technological trend across various landscapes. Similarly, IoT solutions for industry and enterprise are at the forefront of technological advancement. When combined with the other state-of-the-art technologies such as artificial intelligence, 5G networks, and big data, the IoT holds the promise for a more connected technological era. This will significantly transform people's lives in a more fundamental way. There is no doubt that artificial intelligence, when converged with IoT, forms the superpower of innovation for industry and enterprises. Further, without the effective implementation of IoT technology, it is impossible for enterprises to attain the benefits of smart features, functionalities, and enhanced productivity measures. As a result, research on IoT has become significant for industrial and enterprise applications. 'This special issue of the journal "Journal of Internet Technology" entitled "Current Trends and the Future of the Internet of Things (IoT) in Industry and Enterprise," is mainly focused on exploring the innovative applications of IoT technologies for industry and enterprise applications. The collection of papers presented in this section emphasizes several aspects of IoT in business enterprises. The call for papers resulted in the acceptance of five paper submissions. For each submission, a double-blinded review process was conducted, and the papers were selected with appropriate quality measures.
Keywords: internet; loT; industry; enterprise; JCR; Scopus